Linear systems : non-fragile control and filtering - Yang, Guang-Hong. (Taylor & Francis, 2013)
"Designing controllers/filters such that the resulting closed-loop systems are non-fragile or insensitive with respect to the perturbations in the controller or filter coefficients has become an important research topic in many fields of engineering and science. This book develops a systematic presentation of the newly proposed methods for non-fragile/insensitive control/filtering of linear systems with respect to controller/filter coefficient variations. It provides designs and guidelines that can be used to develop advanced non-fragile control techniques to improve reliability, maintainability, and survivability of complex control systems"--